Evaluation of different biochemical markers in prediction of metabolic syndrome in polycystic ovary syndrome patients - Radwan, Ahmed M.; Youssry, Mohamed A.; El-saadany, Hossam M.; Patel, Tabark Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Polycystic ovary syndrome (PCOS) is the commonest cause of chronic hyperandrogenic anovulation. Insulin resistance and compensatory hyperinsulinemia are keys of the pathogenesis of PCOS. It is also considered as a metabolic disorder. Since the components of metabolic syndrome (MBS) namely obesity, glucose intolerance, dyslipidemia, and hypertension are the common features of this syndrome. The association between MBS and PCOS can be explained by different theories as insulin resistance, obesity, and related adipose tissue factors (adipocytokines) independent of insulin resistance are the main pathogenic contributors to both disorders. Methods: A total of 143 women with PCOS were recruited as study subjects. All participants were subjected to anthropometric measurements, clinical assessment, and biochemical tests [fasting glucose, fasting insulin, and homeostatic model assessment-insulin resistance (HOMA-IR)]. Hormonal profile particularly leptin and homocysteine levels were also evaluated. Results: 25 patients (17.4%) out of 143 women with PCOS met the criteria for MBS. Patients with MBS had significantly higher body mass index, blood pressure, HOMA-IR, leptin, and homocysteine levels compared to PCOS only patients. When HOMA-IR cut off was ≥4.3 sensitivity and specificity were 90%, 88.6%, but when leptin level was ≥34.5 the corresponding statistics were 79.6%, 75.5%. Conclusions: Serum leptin, homocysteine, HOMA-IR as well as other biochemical markers are significantly higher in women with PCOS and MBS compared to PCOS only women. PCOS is associated with various factors like insulin resistance, obesity, and dyslipidemia. Consequently, adipocytokines and HOMA-IR play important role in the prediction of MBS in patients with PCOS.